2016
DOI: 10.1016/j.scitotenv.2016.07.041
|View full text |Cite
|
Sign up to set email alerts
|

A half-century of production-phase greenhouse gas emissions from food loss & waste in the global food supply chain

Abstract: Research on loss & waste of food meant for human consumption (FLW) and its environmental impact typically focuses on a single or small number of commodities in a specific location and point in time. However, it is unclear how trends in global FLW and potential for climate impact have evolved. Here, by utilising the Food and Agriculture Organization's food balance sheet data, we expand upon existing literature. Firstly, we provide a differentiated (by commodity, country and supply chain stage) bottom-up approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 12 publications
5
157
0
2
Order By: Relevance
“…The embedded GHG emissions of meat (poultry, bovine, goat, mutton, and swine) estimated by Porter et al (2016), accounted for 34-38% of all FLW production-phase GHG emissions, despite comprising just 3-4% of total FLW by mass. Song et al (2015) highlighted that although only 13% of food wasted in China was animal derived foods, it accounted for 44% of the water embedded in total food waste.…”
Section: Environmental Impacts Of Flwmentioning
confidence: 99%
See 1 more Smart Citation
“…The embedded GHG emissions of meat (poultry, bovine, goat, mutton, and swine) estimated by Porter et al (2016), accounted for 34-38% of all FLW production-phase GHG emissions, despite comprising just 3-4% of total FLW by mass. Song et al (2015) highlighted that although only 13% of food wasted in China was animal derived foods, it accounted for 44% of the water embedded in total food waste.…”
Section: Environmental Impacts Of Flwmentioning
confidence: 99%
“…Porter et al (2016) have identified a 44% increase in global average per capita FLW emissions between 1961 and 2011-from 225 kg CO2e in 1961 to 323 kg CO2e in 2011. During that period, developing countries, particularly China and Latin American countries, produced the largest amount of GHG emissions associated with FLW, mainly from fruit and vegetable losses (Porter et al, 2016).…”
Section: Environmental Impacts Of Flwmentioning
confidence: 99%
“…The increasing attention paid to FW issues is mainly due to its negative environmental, economic and social impacts [3,4]. For instance, the greenhouse gas (GHG) emissions related to the food wasted during the production phase were estimated to be about 2.2 Gt CO 2 equivalent (eq) in 2011 [5], while the costs associated with the wastage were around 143 billion Euro per annum in the EU-28 [2]. In this context, the reduction of FW and the optimisation of its management is a priority for the European Commission, which is working to achieve a significant reduction in FW by 2020 by means of joint actions, in order to obtain a minimisation of loss and waste throughout the whole food supply chain [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Porter et al (2016) based on FAO data, the GHG emissions from FLW in the global food supply chain over the period 1961-2011 were detailed for the relative contribution of FLW-related GHG emissions by commodity and by region. According to the study global annual production-phase GHG emissions associated with FLW more than tripled between 1961 and 2011 (from 680Mt to 2,2Gt CO 2 -eq.).…”
Section: Relation Phm and Climate Footprintmentioning
confidence: 99%
“…This is one of the conclusions from a macro-study on food losses and climate impact by Porter et al (2016). Efforts will have to be geared to acquiring data on losses and GHG emissions on the level of individual supply chains, in order to calculate the climate impact from PHM measures.…”
Section: Informationmentioning
confidence: 99%